When the Room Is Spinning: Experience of Vestibular Neuritis by a Neurotologist - Kim, Ji-Soo (Frontiers in Neurology, 2020)
Vestibular neuritis (VN) is the most common cause of acute prolonged spontaneous vertigo, and is characterized by acute unilateral vestibular hypofunction, probably due to inflammation of the vestibular nerve. The diagnosis of VN may be secured bedside with spontaneous horizontal-torsional nystagmus beating away from the lesion side and abnormal head impulse tests for the semicircular canals involved on the lesion side when other neurological symptoms and signs are not associated. This report describes what a neuro-otologist experienced during an attack of VN and discuss its implications. Transfer of this personal experience would aid in understanding what is felt by the patients during the attacks of vertigo.